1983
DOI: 10.1161/01.atv.3.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Remnants of lipoproteins of intestinal and hepatic origin in familial dysbetalipoproteinemia.

Abstract: We used the low molecular weight form of apolipoprotein B (B-48) as a marker for the identification of remnant particles formed from chyiomicrons in the plasma of patients with familial dysbetalipoproteinemia. In the serum of patients fasted 14 hours, the d < 1.006 g/cm 3 lipoproteins of prebeta mobility, separated by starch block electrophoresis, contained only the primary hepatogenous species of apolipoprotein B (B-100), and their llpld composition resembled that of normal prebeta very low density lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Type III hypercholesterolemia is characterized clinically by the elevation of plasma cholesterol and triglyceride levels, the accumulation of cholesterol-rich ␀-VLDL particles (apoB-48 -containing ␀-VLDL and apoB-100 -containing VLDL remnants) in the plasma, and the formation of lipid deposits in the skin and artery wall. 6,29 In vitro experiments using mouse peritoneal macrophages have shown that the chylomicron remnants are effective in causing cholesteryl ester accumulation in these cells. 30 Recently, transgenic apoB-100 -and apoB-48 -only mice on the apoE-null background were used to study the atherogenicity of apoB proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Type III hypercholesterolemia is characterized clinically by the elevation of plasma cholesterol and triglyceride levels, the accumulation of cholesterol-rich ␀-VLDL particles (apoB-48 -containing ␀-VLDL and apoB-100 -containing VLDL remnants) in the plasma, and the formation of lipid deposits in the skin and artery wall. 6,29 In vitro experiments using mouse peritoneal macrophages have shown that the chylomicron remnants are effective in causing cholesteryl ester accumulation in these cells. 30 Recently, transgenic apoB-100 -and apoB-48 -only mice on the apoE-null background were used to study the atherogenicity of apoB proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1). An increase of remnant lipoproteins is a risk factor for atherosclerosis (2). The remnant lipoprotein is as well as the oxidized low density lipoprotein (LDL), easily taken into the macrophage in the arterial wall, promoting foam cell formation of macrophages and forming the atherosclerotic lesion (Fig.…”
Section: Remnant Lipoproteins and Remnant Like Particles (Rlp)mentioning
confidence: 99%
“…The f3-VLDL include two distinct subclasses of lipoproteins (4,5), which can be isolated by agarose chromatography; they are referred to as fraction I and fraction II. Fraction I consists of large particles (700-800 A in diameter) containing apolipoprotein E (apo-E) and a low molecular weight form of apo-B referred to as B48.…”
Section: -3)mentioning
confidence: 99%